PENGARUH BEBERAPA PERLAKUAN PASCA PANEN DAN SUHU PENYIMPANAN TERHADAP KUALITAS DAN DAYA SIMPAN BUAH PISANG CAVENDISH (Musa (GRUP AAA, SUBGRUP Cavendish)) - Bambang S. Purwoko; Diah Juniarti (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1998)
The objective of this research was to determine the effect of prestorage infiltration of CaCl2, infiltration of spermidine, plastic wrapping and waxing on the maintenance of banana shelflife and qualities at different storage temperatures. Prestorage infiltration of Cavendish banana (Musa Cavendishii) with CaCl2 inhibited fruit softening, the increase of sugar content in peel color index. Plastic wrapping could inhibit the increase of weight loss, pulp peel ratio, peel color index, and the decrease of appearance score. Treatment of fruit with spermidine infiltration store in cool temperature could maintain banana shelflife until 27.8 days or 8.1 days longer than control.